Evaluation of subchronic administration of antiseizure drugs in spontaneously seizing rats. (18th May 2020) - Thomson, Kyle E.; Metcalf, Cameron S.; Newell, Thomas G.; Huff, Jennifer; Edwards, Sharon F.; West, Peter J.; Wilcox, Karen S.
Abstract: Objective: Approximately 30% of patients with epilepsy do not experience full seizure control on their antiseizure drug (ASD) regimen. Historically, screening for novel ASDs has relied on evaluating efficacy following a single administration of a test compound in either acute electrical or chemical seizure induction. However, the use of animal models of spontaneous seizures and repeated administration of test compounds may better differentiate novel compounds. Therefore, this approach has been instituted as part of the National Institute of Neurological Disorders and Stroke Epilepsy Therapy Screening Program screening paradigm for pharmacoresistant epilepsy. Methods: Rats were treated with intraperitoneal kainic acid to induce status epilepticus and subsequent spontaneous recurrent seizures. After 12 weeks, rats were enrolled in drug screening studies. Using a 2‐week crossover design, selected ASDs were evaluated for their ability to protect against spontaneous seizures, using a video‐electroencephalographic monitoring system and automated seizure detection. Sixteen clinically available compounds were administered at maximally tolerated doses in this model. Dose intervals (1‐3 treatments/d) were selected based on known half‐lives for each compound. Results: Carbamazepine (90 mg/kg/d), phenobarbital (30 mg/kg/d), and ezogabine (15 mg/kg/d) significantly reduced seizure burden at the doses evaluated. In addition, a dose‐response study of topiramate (20‐600 mg/kg/d) demonstrated that this compound reduced seizure burden at both therapeutic and supratherapeutic doses. However, none of the 16 ASDs conferred complete seizure freedom during the testing period at the doses tested. Significance: Despite reductions in seizure burden, the lack of full seizure freedom for any ASD tested suggests that this screening paradigm may be useful for testing novel compounds with potential utility in pharmacoresistant epilepsy.